2020
DOI: 10.2147/ppa.s236964
|View full text |Cite
|
Sign up to set email alerts
|

<p>Methods to Assess Patient Preferences in Old Age Pharmacotherapy – A Systematic Review</p>

Abstract: Purpose: The aim of this systematic review was to identify methods used to assess medication preferences in older adults and evaluate their advantages and disadvantages with respect to their applicability to the context of multimorbidity and polypharmacy. Material and Methods: Three electronic databases (PubMed, Web of Science, PsycINFO) were searched. Eligible studies elicited individual treatment or outcome preferences in a context that involved long-term pharmacological treatment options. We included studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 100 publications
(258 reference statements)
1
8
0
Order By: Relevance
“…Only few strategies have been developed and evaluated for the assessment of medication preferences in geriatric multimorbidity. 8 In addition to preference instruments focusing specifically on polypharmacy, a number of studies have touched on medication-related patient priorities as part of larger interventions aimed at providing patient-centered care for older individuals with multiple chronic conditions. [39][40][41] Recently, an approach called Patient Priorities Care has been introduced and studied in an ambulatory setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only few strategies have been developed and evaluated for the assessment of medication preferences in geriatric multimorbidity. 8 In addition to preference instruments focusing specifically on polypharmacy, a number of studies have touched on medication-related patient priorities as part of larger interventions aimed at providing patient-centered care for older individuals with multiple chronic conditions. [39][40][41] Recently, an approach called Patient Priorities Care has been introduced and studied in an ambulatory setting.…”
Section: Discussionmentioning
confidence: 99%
“… 7 Few measurement instruments have assessed medication preferences in the context of geriatric multimorbidity. 8 Examples include a discrete choice experiment evaluating the trade-offs between the risk of fall injury, symptomatic side effects, and the preventive benefits of antihypertensive drug therapy, 9 and a scenario-based approach to measure the patients’ willingness to take medication for the prevention of cardiovascular disease. 10 The so-called Outcome Prioritization Tool, which allows for prioritizing between four universal health outcomes, has been used in several different studies and employed as a starting point to propose medication changes in primary care patients.…”
Section: Introductionmentioning
confidence: 99%
“…Yet beliefs linked to medication treatments are a gateway to understanding the patient rationales underpinning their daily medication use [ 20 ]. Furthermore, most scientific studies have concentrated on specific illnesses and medications in order to explore particular non-adherent behaviours [ 17 ] and patient preferences [ 35 ]. Yet experiences of medication practices and the beliefs that surround them seem to go beyond specific types of medication for chronic illnesses [ 17 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…treatment yes/ no). A recent review regarding preferences in old age pharmacotherapy reported that out of 55 identified instruments the majority of these were designed to assess a patient's preferences in a disease-specific context while only three questionnaires accounted for multimorbidity [7]. Furthermore, only a limited number of these tools focus on prioritization of health outcomes [8].…”
Section: Introductionmentioning
confidence: 99%